Effect of Different Warm-up Methods on Anaerobic Power in Young Women - Ali Reza Amani; Homa Esmaeili; Zahra Aeinparast; Farideh Tari (The Society of Aging and Physical Activity (SAPA), 2016)
Improving anaerobic performance and anaerobic power is the critical aspect on successfully in competitions for many athletes. The purpose of current research was to investigating the effect of various pre-competitions warm-up on anaerobic performance. It has been shown that, differences pre-competitions activity may effect on anaerobic and explosive performance. Effect of general warm-up, without warm-up and warm-up with specific static stretch training were examined on anaerobic power. Twenty four young women were recruited in this research. Subjects (20 ± 2.4 years; 164.91 ± 7.54 cm; 62.04 ± 12.34 kg) were performed three pre-test workouts and in the next step, the Wingate test (30 Second) was used to determination of anaerobic power and fatigue index. Familiar session was performed 48 hours before first test. Data management and analysis was performed by one-way ANOVA repeated measure, using SPSS 20.0. The Result of this study indicated that, there is not significant different on fatigue index and maximum anaerobic power in three conditions (P>0.05). It is interesting to note that 30 seconds anaerobic performance was not affected by pre-competitions activities in three stage of this study.